Population-level impact and herd effects following human papillomavirus vaccination programmes: a systematic review and meta-analysis. - Drolet, Mélanie; Bénard, Élodie; Boily, Marie-Claude; Ali, Hammad; Baandrup, Louise; Bauer, Heidi; Beddows, Simon; Brisson, Jacques; Brotherton, Julia M L; Cummings, Teresa; Donovan, Basil; Fairley, Christopher K; et al. (The Lancet. Infectious diseases, 2015)
Human papillomavirus (HPV) vaccination programmes were first implemented in several countries worldwide in 2007. We did a systematic review and meta-analysis to assess the population-level consequences and herd effects after female HPV vaccination programmes, to verify whether or not the high efficacy reported in randomised controlled clinical trials are materialising in real-world situations.